2020
DOI: 10.1021/acschemneuro.0c00537
|View full text |Cite
|
Sign up to set email alerts
|

Omarigliptin Mitigates Lipopolysaccharide-Induced Neuroinflammation and Dysfunction of the Integrity of the Blood–Brain Barrier

Abstract: The blood-brain barrier (BBB) is an important barrier that separates brain tissue from peripheral blood. The permeability of the BBB can be destroyed by external harmful factors, such as lipopolysaccharide (LPS), which contributes to neuroinflammation and central nervous system diseases. The present study aims to investigate the protective effects of Omarigliptin against LPS-induced neuroinflammation and the underlying mechanism using a series of both in vivo and in vitro experiments. A neuroinflammation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Metformin ( Takata et al, 2013 ), pitavastatin ( Morofuji et al, 2010 ), siponimod ( Spampinato et al, 2021 ), and cilostazol ( Horai et al, 2013 ) possess the ability to strengthen brain endothelial barrier properties through modulating intracellular signaling in physiological conditions. Minocycline ( Yang et al, 2015 ), alogliptin ( Hao et al, 2019 ), zafirlukast ( Zeng et al, 2020 ), siponimod ( Spampinato et al, 2021 ), memantine ( Zhu et al, 2019 ), cilostazol ( Horai et al, 2013 ; Takeshita et al, 2014 ), candesartan ( So et al, 2015 ), perampanel ( Chen et al, 2021 ), lithium ( Ji et al, 2021 ), omarigliptin ( Du and Wang, 2020 ) and 5′-azacytidine ( Kalani et al, 2014 ) restore the barrier function dependently of specific pathological conditions (e.g., hypoxia, etc.). Ruxolitinib ( Takata et al, 2019 ) inhibits activation of pericytes to release inflammatory mediators, resulting in restoration of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin ( Takata et al, 2013 ), pitavastatin ( Morofuji et al, 2010 ), siponimod ( Spampinato et al, 2021 ), and cilostazol ( Horai et al, 2013 ) possess the ability to strengthen brain endothelial barrier properties through modulating intracellular signaling in physiological conditions. Minocycline ( Yang et al, 2015 ), alogliptin ( Hao et al, 2019 ), zafirlukast ( Zeng et al, 2020 ), siponimod ( Spampinato et al, 2021 ), memantine ( Zhu et al, 2019 ), cilostazol ( Horai et al, 2013 ; Takeshita et al, 2014 ), candesartan ( So et al, 2015 ), perampanel ( Chen et al, 2021 ), lithium ( Ji et al, 2021 ), omarigliptin ( Du and Wang, 2020 ) and 5′-azacytidine ( Kalani et al, 2014 ) restore the barrier function dependently of specific pathological conditions (e.g., hypoxia, etc.). Ruxolitinib ( Takata et al, 2019 ) inhibits activation of pericytes to release inflammatory mediators, resulting in restoration of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Omarigliptin is a novel once-weekly dipeptidyl peptidase-4 (DPP-4) inhibitor developed for the treatment of type 2 diabetes ( Biftu et al, 2014 ). Studies have found that Omarigliptin can not only maintain the integrity of the BBB by inhibiting neuroinflammation, but also reduce the expression of MMP-2 and MMP-9 to protect TJs protein ( Du and Wang, 2020 ). These results suggest that, for the management of sepsis patients in intensive care unit (ICU), attentions should also be paid to the blood glucose changes and the application of insulin, to reduce the likelihood of SAE ( Huang et al, 2020a ).…”
Section: Bbb and Saementioning
confidence: 99%
“…LPS has also been reported to cause oxidative stress by increasing ROS generation [24]. ROS are closely associated with neurological diseases and are a key mediator in promoting inflammatory response and BBB destruction [26]. A number of experimental studies have shown that an excessive increase in ROS reduces the expression of tight junction proteins in endothelial cells, which increases BBB permeability and causes nervous-system-related diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%